2013
DOI: 10.1111/jai.12141
|View full text |Cite
|
Sign up to set email alerts
|

Stock structure analysis ofLabeo rohita(Hamilton, 1822) across the Ganga basin (India) using a truss network system

Abstract: Summary In this study the intraspecific variation of wild Labeo rohita was investigated on the basis of morphometric characters using the truss network system constructed from the fish body. Altogether 435 fish samples were collected from six drainages of the Ganga basin in India. Data were subjected to principal component analysis, discriminant function analysis and univariate analysis of variance. The first principal component (PC1) explained 47.88% of the total variation, while PC2 and PC3 explained 17.22 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 28 publications
3
38
0
Order By: Relevance
“…The results derived from the allometric method were confirmed by testing the significance of the correlation between the transformed variables and standard length (Mir et al 2013b). Univariate analysis of variance (ANOVA) was performed for 30 morphometric characters to evaluate the significant difference among the three locations.…”
Section: Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…The results derived from the allometric method were confirmed by testing the significance of the correlation between the transformed variables and standard length (Mir et al 2013b). Univariate analysis of variance (ANOVA) was performed for 30 morphometric characters to evaluate the significant difference among the three locations.…”
Section: Methodsmentioning
confidence: 81%
“…Thus, the different current pattern of these water bodies may be playing an important role in modifying the morphometry of S. plagiostomus among these water bodies. A study by Mir et al (2013b) demonstrated morphological variation in the caudal area in a cyprinid, Indian major carp, Labeo rohita (Hamilton, 1822), from six drainages of Ganges basin differing in current velocity. Khan et al (2013) have also found variation in the caudal area of a Channidae fish, Channa punctata (Bloch, 1793), from the Ganges basin in India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a central theme in fisheries science and management (Cadrin, Friedland, & Waldman, 2004;Mir, Sarkar, Dwivedi, Gusain, & Jena, 2013a). Stock identification can be viewed as a prerequisite for any fishery analysis, just as population structure is considered a basic element of conservation biology (Thorpe et al, 1995).…”
mentioning
confidence: 99%
“…Studies of morphologic variation among populations still have an important role to play in stock identification, despite the advent of biochemical and molecular genetic techniques, which accumulate neutral genetic differences between groups (Mir, Sarkar, Dwivedi, Gusain & Jena, 2013). Studies on age and growth, maturity of commercially important fishes, provide baseline information that typically assists with the initial recognition and delineation of geographic regions that are representative of individual stocks (Pawson & Jennings, 1996) and is an almost essential prerequisite for successful stock identification (Griffiths, 1997).…”
mentioning
confidence: 99%